Transformational Leadership of School Principals in Fostering Student Independence at Vocational High Schools in Oku Timur - Suharningsih, Lili; Sumardjoko, Bambang; Sutyamini (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: The education sector faces the challenge of fostering not only academic excellence but also essential life skills, particularly independence. This study addresses the pressing issue of vocational high school (SMK) graduates in Indonesia, who often struggle with adaptation to the workforce and possess inadequate entrepreneurial skills. The research investigates the transformational leadership role of school principals in promoting student independence within Eastern OKU Regency's vocational schools. Purpose: The primary purpose of this study is to explore how principals' transformational leadership can effectively contribute to developing independent, responsible, and decision-making students. This research presents a novel perspective by directly linking transformational leadership practices to student independence, particularly in the context of vocational education, a relatively underexplored area. Novelty: This research has novelty in directly linking transformational leadership practices with aspects of student independence in the context of vocational education. In addition to making theoretical contributions to the development of educational leadership science, this research also offers a contextual approach that is relevant to the dynamics of education in the region. Research Methods: Employing a mixed-methods approach, the study integrates qualitative interviews with school principals and quantitative surveys from students to gather comprehensive data on leadership impacts on student character development. Research Contributions: The contributions of this research are multifaceted. Practically, it offers actionable insights for school principals to enhance their leadership strategies in fostering student independence. The findings are also intended to inform educational policymakers and curriculum developers, promoting responsive vocational education policies that align with contemporary labor market demands